Datafied news work: A scoping literature review - Kammer Aske; Kristensen Lisa Merete; Petrucci Elisabetta (Nordicom Review, 2025)
This article presents a scoping review of 20 years of research literature on datafied news work, synthesising and discussing the scholarly knowledge of how the news industry makes use of digital data. The review is structured around the five “spaces of datafication” of the news industry, which allows for a holistic look at datafied news work and for accounting for the different uses of data in different areas of the organisations. Our dataset consists of 32 peer-reviewed publications on datafied news work, which have been identified through a combination of a systematic literature search in the Scopus database and a systematic sampling of key non-indexed Nordic journals and publishers. The scope is Nordic, situating the notion of datafied news work in the media-systemic context of the democratic corporatist model. In conclusion, what the research shows is that while different kinds of data are used across news organisations, data are consistently regarded as a resource; what changes, dependent upon the specific organisational context, is the understanding of when and how they constitute resources.